The Commutators of Fractional Integrals on Generalized Herz Spaces - Yue Hu; Yuexiang He; Yueshan Wang (Journal of Function Spaces)
Let Il be the fractional integral, 0<l<n and let b∈BMO. We will obtain the weighted estimates for the commutator b,Il on the generalized Herz spaces.